Analisis Tafsir Ilmi terhadap Ayat Singa dalam QS. Al-Muddatsir ayat 51 serta Penafsiran dan Hikmahnya - Muhamad Rulyawan Sihab; Joan Rifky Maulana; Akhmad Dasuki (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the interpretation of the Qur’anic verse mentioning the lion in QS. Al-Muddathir [74]: 51 through the approach of tafsir ilmi (scientific exegesis). The aim of this research is to analyze the theological meaning of the term qaswarah, explore the interpretations of classical and contemporary exegetes, and relate them to the perspective of animal science as well as the underlying wisdom. This study employs a qualitative method with a library research approach, using primary sources from Qur’anic verses and classical tafsir works, and secondary sources from books, journal articles, and relevant scientific literature. The results show that the term qaswarah in QS. Al-Muddathir [74]: 51 has various interpretations, such as lion, hunter, or something frightening. However, most exegetes tend to interpret it as a lion due to its relevance to the context of the parable in the verse. The parable illustrates people who turn away from the truth like wild donkeys fleeing in fear from a predator. From the perspective of tafsir ilmi, this depiction aligns with scientific facts that identify the lion as an apex predator capable of triggering a fight-or-flight response in prey animals. Furthermore, the mention of the lion in the Qur’an is not merely descriptive but also contains theological, ecological, moral, and psychological values. The lion serves as a symbol to describe irrational human behavior in rejecting the truth. Thus, tafsir ilmi demonstrates a harmonious relationship between revelation and science, where natural phenomena are used as a medium to convey profound moral and spiritual messages.